Oxidative Status and Histopathological Changes in Broilers Infected with Salmonella Pullorum and Treated with Bacillus Subtilis, Organic Acids and Ciprofloxacin - Abdulwahhab, Abeer I.; Baker, Mushtaq T. (Diyala Journal for Veterinary Sciences, 2023)
The goal of the study was to compare the effects of three different medications, a probiotic, an organic acid, and ciprofloxacin on oxidant status and histopathological alterations during the starter phase of broiler challenge with Salmonella pullorum. A total of 250 (Ross 308) one day old broiler chicks were separated into five groups, each with 50 chicks. All groups, excepted group five, were orally challenged with Salmonella pullorum 0.2 ml (25×104 CFU/ml) isolate (OM988162.1) at one day old. First group (G1): challenged with Salmonella pullorum and treated with Bacillus subtilis (2×107 CFU/g) (250 g/1000 L) in drinking water; second group (G2): challenged and treated with organic acid (0.5-1 ml/L) in drinking water; third group (G3): challenged and treated with ciprofloxacin 10% (0.5 ml/L) in drinking water; fourth group (G4): challenged without treated as (control positive) and fifth group (G5): unchallenged and untreated as (control negative). The findings indicated an occurrence of highly substantial variations at level (P ≤0.05) of the oxidative status in serum after 7, 21, and 35 days following the challenge with Salmonella pullorum, which revealed an increase in the means of H2O2 and LPO in serum for all groups in comparison with the control group. When compared to G5, G2 seems to have the greatest mean of antioxidant GSH-px in serum, however, were considerably lower in G4 and G1 at level (P≥ 0.05), followed by G3. The histopathological analysis performed at day 21 after infection revealed that S. pullorum-a alone infected group (G4) noticed shortening and structural disturbance of the gut, whereas organic acid maintained a mostly unaltered shape and notably boosted intestinal villus height in G2, along with mild perivascular MNCs cuffing and slight hepatocyte vascular degeneration. We conclusion, the organic acid has biggest role in protection compared to ciprofloxacin that have immunosuppression. Also, B. subtilis not recorded any protection.